KAJIAN ASPEK PSIKOLOGI SENAM KESEGARAN JASMANI, SEBUAH STUDI KASUS PADA SENAM KEARIFAN LOKAL - Susy Purnawati; Luh Made Sri Handari Adiputra; Luh Putu Ratna Sundari; I D A P Inten Primayanti (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2018)
AbstractBackground: Emotions or feelings among sports participants need to get attention because emotions in addition to affecting other psychological aspects (mind and desire) also affect the physiological aspects. Method: This preliminary study was an observational (cross sectional analytic) study conducted in April 2018 in Denpasar that combined observations, interviews among key informant person (to collect the qualitative data) and quantitative data collection used a Task and Ego Orientation in Sport Questionnaire (mixed method). Result: The results of this study showed an emotional reaction that emerged as the effect of doing Senam Janger exercises was very positively. The focus of attention on gym movements, traditional gamelan accompaniment that reminds spiritual nuances, as well as aerobic exercise effects in the zones target of exercise can provide a sense of excitement and mental calm. The gymnastics activity within group have an effect on social interaction that can lead to competitiveness attitudes. The effect occurs by the presence of other persons factor or presence of others. Conclusion: Senam Janger exercise -from the psychological aspect- create an effect of positive emotional reactions (joy, less tension), but in this study has not been proven its effect on increased confidence and superior feeling in competing due to very small sample size.Keywords: general gymnastics, psychological aspects, positive emot